Formulación de un emprendimiento de asesoría contable y tributaria en la ciudad de Caluma, cantón Caluma – provincia Bolívar en el año 2017 - Averos Arias, Jessica Paola (2017)
Through this report of the work of entrepreneurship, which has as an idea to undertake to promote a tax culture and provide tools for the proper handling of documentation, in order to avoid any inconvenience that may arise, so it was necessary to conduct research thus confirming the need of the commercial sector to comply with its tax obligations, which involves professional taxpayers or advisory offices to keep up to date their tax obligations and accounting records in order to avoid fines or financial penalties by the governing body as it is the Internal Revenue Service, so it is evident that taxpayers keep their accounts in an empirical manner which causes loss of information and even missing documents that are evidence of commercial activity. The research on entrepreneurship work was carried out in the canton Caluma, calculating the sample of the active population in the Internal Revenue System of Ecuador (SRI), which belongs to the canton of Caluma, using books as a theoretical base, quality management system to the service of technical cooperation, successful entrepreneurship how to improve its process and management in order to facilitate the management of the subject under investigation. The current study made it possible to delimit that currently in the city of Caluma there is an accounting and tax advisory office which implies that it does not satisfy the need of the entire commercial group of the city, therefore the implementation of the Entrepreneurship "Creation of an Accounting and Tax Advisory Office", as an efficient alternative in the canton. The accounting and tax advisory endeavor will contribute to the stimulation of new ventures, to independent work; and, to the generation of new jobs.